Caracterização molecular e avaliação da infectividade in vitro e in vivo de duas cepas de Leishmania spp. isoladas de cães naturalmente infectados - Oliveira, Marco Miguel de (2018)
Leishmaniasis can take on two main clinical forms: visceral leishmaniasis (VL) and cutaneous leishmaniasis (LC). In urban areas, the dog participates as a reservoir of Leishmania infantum (causing LV) and, because of this, is the target of the disease control strategies. These animals can also be found naturally infected by the species that lead to the development of LC. Although these infections are rare, some findings in the literature have opened the question about the role of these animals in the biological cycle of these species and their infective potential. Thus, it becomes important the molecular characterization and evaluation of the infective behavior of these parasites. The present study aimed to identify the species of two wild strains isolated from dogs from the city of Uberlândia (MG), as well as the evaluation of their in vitro behavior and infectivity to canine macrophages of commercial lineage and BALB / c mice. To this end, the amplification products of the ITS1 and hsp70 targets of Leishmania spp. were subjected to enzyme restriction (PCR-RFLP). The in vitro proliferation profile was established by the growth curve, with UDI-1 and UDI-2 being compared to two reference strains, Ba199 (MHOM/BR/1989/Ba199 - L. amazonensis) and BH401 (MCAN/BR/2002/BH401 - L. infantum). In vitro infectivity experiments were performed using macrophages (DH82), as well as promastigotes of stationary phase and axenic amastigotes of wild and reference strains. In vivo evaluation of the infection was verified by analyzing the parasite load in the liver, spleen and lesions of mice infected with the four parasite strains (UDI-1, UDI-2, Ba199, BH401). In addition, the infection kinetics were verified by weight monitoring, lesion size and behavior. The results of PCR-RFLP showed that UDI-1 presented a profile of pairs of bands similar to L. amazonensis and UDI-2 to L. infantum. The in vitro behavior differed between UDI-2 and BH401, being similar between UDI-1 and Ba199. Stationary phase promastigotes of UDI-1 showed the highest infectivity capacity compared to the other strains, and when using axenic amastigote forms, BH401 was the strain with the highest infectivity index. In both cases, UDI-2 showed the lowest infectivity in vitro. In vivo, UDI-1 induced lesions more rapidly (three weeks) and had a higher mean parasitic load on lesion and liver compared to Ba199. The metastatic phenotype was verified, with consequent visceralization of UDI-1. In contrast, the mean values of the parasitic load of UDI-2 were lower than those of BH401 in the evaluated tissues (liver and spleen). No behavioral changes and no natural gain were observed. Together, these data show that among the wild strains, UDI-1 shows the best infectivity capacity in vitro and in vivo, and UDI-2 exhibited the least infective phenotype. In addition, this is the first report on the natural infection of a dog with L. amazonensis in the Triângulo Mineiro (MG) region.